2015
DOI: 10.1080/00986445.2015.1023300
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optimization of 2-ethylhexyl Ester as Base Oil for Drilling Fluid Formulation

Abstract: A stable ester was synthesized to overcome the ester hydrolysis problem during the drilling of oil or gas wells using a conventional ester-based drilling fluid. The thermal and hydrolytic stability of the produced ester was high owing to the transesterification method employed in this study. The reaction was performed using 2-ethylhexanol and methyl laureate esters in the presence of sodium methoxide as a catalyst. In order to obtain the optimum synthesis conditions, a response surface methodology (RSM) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Habib et al (Abdul Habib et al 2014) studied 2-Ethylhexyl oleate based drilling fluid which showed excessive viscosity. On the other hand, 2-Ethylhexyl laurate-based drilling fluid exhibited better drilling fluids performance after 16 hours of dynamic ageing at 250 °C (Jassim et al 2016).…”
Section: Hydrolysis Process Of Biodiesel Under (A) Basic Conditions A...mentioning
confidence: 94%
See 2 more Smart Citations
“…Habib et al (Abdul Habib et al 2014) studied 2-Ethylhexyl oleate based drilling fluid which showed excessive viscosity. On the other hand, 2-Ethylhexyl laurate-based drilling fluid exhibited better drilling fluids performance after 16 hours of dynamic ageing at 250 °C (Jassim et al 2016).…”
Section: Hydrolysis Process Of Biodiesel Under (A) Basic Conditions A...mentioning
confidence: 94%
“…and 10 min.) were in lbf/100 ft 2 , plastic and apparent viscosity were in cP and fluid loss was in ml) Most of the above mentioned studies faces one common issue that the formulation of drilling fluids usually contains lime to activate the emulsifier Muller H, Herold C, Von Tpavicza S, Grimes DJ, Braun J-M 1992;Jassim et al 2016). If lime content increases to 3 g per 350 ml of mud, the EBDF will have unstable properties due to ester's hydrolysis .…”
Section: Hydrolysis Process Of Biodiesel Under (A) Basic Conditions A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 0.5 ml of N, O-Bis (trimethylsilyl) trifluoroacetamide was added into the vial and mixed this mixture thoroughly. Before injecting into the GC machine, this prepared sample was first heated at 40°C for 10 min and then cooled to normal room temperature (Jassim et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic based muds are tailored to mirror the superior technical performance of oil based muds while eliminating the environmental hazards associated with the later. Furthermore, synthetic base fluids from which these muds are formulated contain zero percent aromatic hydrocarbons [7], they can be discharged into the environment without any deleterious effect [8]. This is in addition to the fact that their reduced irritant properties lead to improved workers' safety [9].…”
Section: Introductionmentioning
confidence: 99%